Training On The Making Of Solid Soap By Utilizing Used Cooking Oil Waste By Pembinaan Kesejahteraan Keluarga (PKK) Women In Wangen Village - Tatiana Siska Wardani; Erna Chotidjah Suhatmi (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
Social welfare can be improved in various ways that can be done, for example, through community empowerment programs. The part of the community that can be empowered are housewives who are members of the PKK organization, especially in Wangen Village, Polanharjo District, Klaten Regency. The impact of environmental pollution is due to the disposal of used cooking oil and is followed by an increase in the use of cooking oil due to the appeal to stay at home during the Covid-19 pandemic. The existence of this makes a training program and assistance for the utilization of cooking oil waste into soap is the right thing to deal with this problem. The specific goals and targets to be achieved in this activity are that PKK mothers are interested and motivated to become entrepreneurs, to form groups of PKK members who become economically independent by producing soap. In order to achieve this goal, a community service program was carried out by a lecturer at the University of Duta Bangsa Surakarta who provided soap production training conducted by PKK women in Wangen Village. The result of this service is an increase in the skills of PKK Village women in Wangen in making soap from used cooking oil waste.